Online Training in Specific Meditation Practices Improves Gratitude, Well-Being, Self-Compassion, and Confidence in Providing Compassionate Care Among Health Professionals - Nisha Rao BA; Kathi J. Kemper MD, MPH (SAGE Publishing, 2017)
Mind-body practices that intentionally generate positive emotion could improve health professionals' well-being and compassion. However, the feasibility and impact of clinician training in these practices is unknown. Data were analyzed from 3 online modules offered to health professionals: ( a ) Gratitude, ( b ) Positive Word, and ( c ) Loving-kindness/Compassion meditation. Paired t tests were used to assess pre- to posttraining changes in gratitude (Gratitude Questionnaire), well-being (World Health Organization Well-Being Index), self-compassion (Neff's Self-Compassion Scale), and confidence in providing compassionate care (Confidence in Providing Calm, Compassionate Care Scale). The 177 enrollees included diverse practitioners (nurses, physicians, social workers, and others). Training was associated with statistically significant improvements in gratitude (38.3 ± 4.6 to 39.5 ± 3.3), well-being (16.4 ± 4.0 to 17.9 ± 4.2), self-compassion (39.5 ± 8.1 to 43.1 ± 7.6), and confidence in providing compassionate care (73.3 ± 16.4 to 80.9 ± 13.8; P < .001 for all comparisons). Brief, online training appeals to diverse health professionals and improves their gratitude, well-being, self-compassion, and confidence in providing compassionate care.